College students’ satisfaction with online teaching during the COVID-19 pandemic: Evidence from Hubei Province, China - Yanzhong Huang; Zhongbo Xiong; Di Liu; Yan Zhang (Heliyon, 2024)
To evaluate the performance of online teaching during the COVID-19 period, we collected 1886 survey data from college students in Hubei Province, China. The scoring rules of the Framework for Teaching were used to measure college students' satisfaction with online teaching, and an econometric model was constructed to empirically validate its dynamic influences. We found that college students' satisfaction with online teaching during the COVID-19 pandemic was lower than that with offline teaching. Online teaching satisfaction was significantly affected by variables of class size, proportion of online teaching, epidemic severity, college grade, network, course classification, major classification, and the teacher's age and skills. It was further found that as COVID-19 gradually dissipated, offline teaching should be resumed as soon as possible. These findings objectively evaluate the teaching performance of college students during the COVID-19 pandemic and can provide suggestions for optimizing online teaching during future emergencies.